The Classical Book of the Abbasid Period as a Reference for Advanced Military Technology: A Thought Genealogy Study - Pramono, Agus (Universitas Islam Negeri (UIN) Salatiga, 2022)
The most effective metal manufacturing process is double pressing, which is capable of bending metal. The bending of the metal will cause a reaction that can improve its mechanical properties. In the book Al-Jamahir fi ma`rifat al-Jawahir there are three patterns that explain the process methodology, they are; لملك Al mil'k: Tension, الفقلو Al Fiqlu: bending, اإلنفيل Al infial: Reaction. This is in line with the development of the equal-channel angular pressing (ECAP)’s method: if the metal is bent, a reaction will occur which can improve its mechanical properties. In Kitab Al-Hiyal there is a hypothesis of the existence of an attraction in the movement of celestial bodies which is able to provide an explanation of the movement of large forces. Then, another discussion is about the motion of stars and the law of attraction, where there is a force of attraction between celestial bodies. According to the book of Al Hiyal, the greatest force is the earthquake movement which causes a circular rotary force effect, this also underlies the high pressure torsion (HPT) method by PW Bridman who discovered the HPT method with a narrative that HPT is initiated by earthquake movements and in his scientific article explains that the earthquake movement as a torsional motion. In another experimental reference, accumulative roll bonding (ARB) technology is the basis of the material development method which is carried out by stacking plates that are loaded with roll compression loads. Based on the double-edged sword experiment, the zulfikar sword, which is explored by Khabab bin Art as a practitioner and Salman Al Farishi as a drafter, this method has similar procedures for stacking and finalizing the base plate. The development of the Zulfikar sword continued with Al Qashhandi who developed the Damascus sword used by Salahuddin Al Ayubi, from the perspective of the metal plate bending stress originating from the roll compression stress, where there is a deflection of the tip of the plate on the blade. The results of the characterization of the ECAP, HPT and ARB methods show that HPT has superior mechanical properties characterization results compared to other methods, but HPT has limited dimensions which can only be applied to components that have a size of less than 5 cm, with a powder base material. Meanwhile, ECAP and ARB dominate in many applications because they can be applied to large dimensions, as well as the availability of materials and the flexibility of raw materials into application products.